Head-Toes-Knees-Shoulders task and EF in two samples of adolescents in Brazil and United States - Fernandes, Valter R.; Becker, Derek R.; McClelland, Megan M.; Deslandes, Andrea C. (Frontiers in Psychology, 2023)
Executive function (EF) is a foundational cognitive construct, which is linked to better cognitive and physical health throughout development. The present study examines the construct validity of an EF task, the Head-Toes-Knees-Shoulders task (HTKS) that was initially developed for young children, in a sample of adolescents. We investigate the initial validity and range in scores between 54 adolescents from Brazil (mean age 12.58) and 56 U.S. adolescents (mean age 12.48) from different socioeconomic contexts. Results indicated that the HTKS showed sufficient variability in both samples, especially for a measure of HTKS efficiency (completion time divided by the total score). The U.S. sample performed better on all cognitive measures. For the Brazilian sample, regression models controlling for age and sex showed a significant relationship between the digit span working memory task, the HTKS total score, and the HTKS efficiency score. The Heart and Flowers cognitive flexibility measure was also included as an independent variable only for the Brazil sample, showing a significant relationship with both HTKS scores. For the U.S. sample, results showed that only the HTKS efficiency score was significantly related to the digit span working memory task. This study highlights the importance of cognitive efficiency measures to achieve greater validity, as they can assess a broader range of performance with different populations. The HTKS showed good ecological validity with two adolescent samples, as it differentiated between populations with high and low socioeconomic status from different cultural contexts.